INTESTINAL TRANSPLANTATION - Tzakis, Andreas G. (1994)
Intestinal transplantation is often the only alternative form of treatment for patients dependent on total parenteral nutrition for survival. Although a limited number of intestinal transplantations have been performed, results with FK 506 immunosuppression are comparable to those for other organ transplants. The impact of successful intestinal transplantation on gastroenterology will likely be similar to the impact of kidney and liver transplantation on nephrology and hepatology.